Analyzing the Influence of Dividend Policy on Corporate Value: A Financial Perspective with Haier as a Case Study - Danni, Wang; Qi, Zhong (Journal of Accounting, Business and Management (JABM), 2024)
The dividend policy plays a pivotal role in stabilizing stock prices and sustaining investor enthusiasm for listed companies. It not only significantly impacts the interests of management, investors, and creditors but also has long-term implications for the company's development. However, most studies on Chinese enterprises' dividend policies primarily rely on empirical research methods, with limited literature available on individual companies. The utilization of a case analysis methodology in this study has significantly enhanced the research cases related to China's dividend policies, thereby providing valuable insights for the advancement of analogous industries and the formulation of future dividend policies. In this study, Haier Smart Home Co., Ltd. (referred to as "Haier"), a publicly traded company on the Shanghai Stock Exchange, is selected as the case study subject in order to examine the impact of dividend policy on corporate value from a financial perspective. Through an analysis of Haier's dividend allocation data from 2008 to 2022 and an evaluation of various financial indicators during this period, we find that a stable dividend payment level can effectively sustain the enterprise value of the company. Therefore, it is recommended for listed companies to optimize their ownership structure and enhance corporate governance while strategically formulating dividend policies aligned with their financial performance and corporate strategy.